Provider and patient perception of psychiatry patient health literacy - Bacon O (Pharmacy Practice, 2017)
Background: Inadequate health literacy in adults is a nationwide issue that is associated with worse health outcomes. There is a paucity of literacy regarding rates of inadequate health literacy in psychiatric populations. Objective: The aim of the study was to identify an existing tool that would easily identify patients who had inadequate health literacy, so that a targeted intervention could be performed. Secondarily we attempted to compare rates of inadequate health literacy with providers’ perception of patients’ health literacy. Methods: We assessed health literacy in a psychiatric population by administering the Brief Health Literacy Survey (BHLS). Additionally, all psychiatry residents, psychiatrists, nurse practitioners, pharmacists, and social workers were surveyed to assess their perception of patient health literacy. Differences between patient health literacy and provider expectations of patient health literacy were compared. Results: Inadequate health literacy was identified in 31 out of 61 patients (50.8%) using 2 questions from the BHLS. Only 9 (29%) of patients who were identified as having inadequate health literacy were identified by both BHLS questions. In contrast, almost 100% of providers identified their patients, in general, as having inadequate health literacy. Conclusions: These results identify a higher rate of health literacy in a psychiatric inpatient population than in the general population. However, providers at this institution likely over-identify health literacy. This highlights the need for a health literacy tool that can easily target patients with inadequate health literacy for an intervention.